2023
DOI: 10.1108/ijebr-02-2022-0207
|View full text |Cite
|
Sign up to set email alerts
|

Digital ethnicity affordances: from a liability to an asset in immigrant entrepreneurship

Abstract: PurposeThis paper aims to understand how immigrant entrepreneurs use digital opportunities to overcome the liability of newness and foreignness and how an immigrant's ethnicity can be digitally performed as an asset in business.Design/methodology/approachThe study adopts an inductive multiple case study approach using social media content. The data consist of over 3,500 posts, images and screenshots from Facebook, Instagram and the webpages of seven successful Vietnamese restaurants in Sweden. Grounded content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…In respect of differences that Smallbone et al (2005) allude to, earlier studies feature a variety of issues influencing Coopetition and competitororiented activity entrepreneurs from ethnic minority backgrounds to enter self-employment together with potential problems and inconsistencies in comparison to the wider population (Aliaga-Isla and Rialp, 2013;Hagos et al, 2019). In fact, immigrants typically face what has been termed the liability of newness and foreignness (Evansluong et al, 2023). Illustrations of barriers have existed for some time and include racism and unequal gender relations (Chreim et al, 2018); access to finance together with the potential need to borrow from family and community members (Ram et al, 2002b;Irwin and Scott, 2010); also, a lack of focus and consistency in the support available (Ram and Smallbone, 2003;Fallon and Berman Brown, 2004) [2].…”
Section: Family-ownership and Coopetitionmentioning
confidence: 99%
See 1 more Smart Citation
“…In respect of differences that Smallbone et al (2005) allude to, earlier studies feature a variety of issues influencing Coopetition and competitororiented activity entrepreneurs from ethnic minority backgrounds to enter self-employment together with potential problems and inconsistencies in comparison to the wider population (Aliaga-Isla and Rialp, 2013;Hagos et al, 2019). In fact, immigrants typically face what has been termed the liability of newness and foreignness (Evansluong et al, 2023). Illustrations of barriers have existed for some time and include racism and unequal gender relations (Chreim et al, 2018); access to finance together with the potential need to borrow from family and community members (Ram et al, 2002b;Irwin and Scott, 2010); also, a lack of focus and consistency in the support available (Ram and Smallbone, 2003;Fallon and Berman Brown, 2004) [2].…”
Section: Family-ownership and Coopetitionmentioning
confidence: 99%
“…, 2019). In fact, immigrants typically face what has been termed the liability of newness and foreignness (Evansluong et al. , 2023).…”
Section: Theoretical Developmentmentioning
confidence: 99%
“…The work of Evansluong et al (2023) has shown that for many immigrant entrepreneurs, there is a significant barrier to success caused by a lack of digitization. This barrier is typically formed from a lack of exposure to modern digital technologies, or else, a lack of capital with which to buy the appropriate hardware to become digitized.…”
Section: Finding a Nichementioning
confidence: 99%
“…For immigrant entrepreneurs to succeed, Evansluong et al (2023) have identified 3 stages of digital ethnicity affordance. The first is the conversion of offline content into online content, digitizing products, services, and successfully representing their business venture using technology.…”
Section: Finding a Nichementioning
confidence: 99%
“…The content of these trainings may be the development of organizational routines and capabilities, the advantages of inter-firm alliances and the development of internationalization and export activities (Mukherjee et al ., 2021). In this way, the problems experienced by new enterprises due to liability newness are eliminated, and they can ensure their sustainability (Evansluong et al ., 2023). In this respect, our findings provide arguments for policymakers to design public policies and institutions that support economic development policies.…”
Section: Implications and Conclusionmentioning
confidence: 99%